PELAKSANAAN PEMBINAAN BIROKRASI LOKAL DI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGITAHUN 2014 - Aprianida, Rosy; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The title of this research is Implementation Guidance Bureaucracy Local In District Cerenti Regency Kuantan Singingi Based on the discovery of the phenomenon that occurred in the field that there are still employees who work not in accordance with the rules that exist as employees who are not honest and careful, Officer Head Cerenti not put the interests state or governance in order to run properly. They are more concerned with their own interests, not excited employees in the District Cerenti work so theres always a delay to the maintenance done by society, and lack of supervision Head coaching in regulating discipline employees, because the home office working hours also still many employees who violate the rules.The problem of this research is How Implementation Guidance Local Bureaucracy in District Kuantan District Cerenti Singingi 2014.The type used in this research is descriptive qualitative survey techniques. The location of this research is done in Kuantan District District Office Cerenti Singingi. Informants are Singingi Kuantan District Secretary, Head of BKD, Head Cerenti, Secretary Cerenti the District, the District Officer Cerenti.The results of the study Implementation Guidance Bureaucracy Locally in Sub Cerenti Regency Kuantan Singingi has not done well and perfect for the run, there are several processes that coaching is done running properly is Giving guidance, Directing, provide education and training, provide instructions, and Giving guide there are some indicators that are not carried out by the district head to direct the local bureaucracy is based on research results of the indicators mentioned in the provision of guidance, mentoring and itruksi-instructions. Yet undone properly because there is still an employee nga melakkan infringement of several of these indicators.Keywords: Implementation, Development, Local Bureaucracy,